HUBUNGAN PENGGUNAAN KELAMBU INSEKTISIDA DENGAN PENULARAN INFEKSI MALARIA DIWILAYAH KERJA PUSKESMAS PENIMBUNG - Ni Nyoman Santi Tri Ulandari; Rauhul Akmam; Nurul Ilmi; Sukardin; Ageng Abdi Putra (LPPM STIKES Mataram, 2025)
Introduction: the Penimbung Public Health Center is one of the health centers located in a malaria-endemic area in West Lombok Regency. Malaria remains a contagious disease that continues to pose a widespread public health issue. Secondary data from the Penimbung Health Center recorded 61 cases of malaria in 2022. The use of insecticide-treated bed nets (ITNs) is considered an sffective method to prevent mosquito bites that transmit malaria. Research Objective: This study aims to investigate the correlation between the use of insecticide-treated bed nets and malaria infection transmission in the service area of the Penimbung Health Center. Research Method: This study employed a cross-sectional design. The study population included families of confirmed malaria patients who had been provided with insecticide-treated bed nets by the penimbung health center. A total of 24 participants were selected using accidental sampling. Data analysis was perform using the chi-square test with fisher’s alternative test. Results: The analysis revealed that 62.5% of the 24 respondents reported not using insecticide-treated bed nets, furthermore, malaria testing showed that 54.2% of the respondents were positive for malaria. A statistically significant association was found between the use of insecticide-treated bed nets and malaria incidence (p=0.000). Conclusion: Based on the results, it can be concluded that there is a significant correlation between the use of insecticide-treated bed nets and the transmission of malaria infection (P=0.000).